Pengaruh Expressive Arts Therapy terhadap Self-Acceptance Narapidana Kasus Narkoba - Onny Fransinata Anggara; Acep Ovel Novari Beny (Personifikasi: Jurnal Ilmu Psikologi, 2023)
Drug abuse is a serious problem in many countries, including Indonesia. Drug convicts have a high risk of experiencing mental health problems and difficulties in accepting themselves, which can affect the rehabilitation process. Expressive arts therapy has been used as an additional therapy to improve individual mental well-being and can be an alternative choice to increase self-acceptance. This study aims to evaluate the impact of expressive arts therapy on the level of self-acceptance of prisoners who experience drug cases. Expressive arts therapy includes aspects of self-expression that can trigger positive emotions, reduce stress, and indirectly increase self-acceptance. This therapy is carried out in groups to strengthen social support, which is a key factor in increasing self-acceptance according to Ryff (2005). This study used a pretest posttest control group design with the participation of 50 drug convicts (25 participants as an experimental group and 25 participants as a control group). This study also used an adapted self-acceptance scale as a measurement instrument. Data analysis was performed using the t test using SPSS software version 22.0. The results show that there is an effect of expressive arts therapy on self-acceptance as indicated by the t test result of 0.034. Furthermore, based on the effectiveness test using the Cohen formula, it is known that expressive arts therapy has a role in the medium or medium category to increase self-acceptance in drug case convicts with an effect size score of 0.6. As a recommendation expressive arts therapy can be an effective alternative therapy to help drug convicts in their recovery process.